A One-Pot, Three-Component Synthesis of 3-(1H-Pyrazol-1-yl)-4H,7H-[1,2,4,5]tetraazino[6,1-b][1,3]benzoxazin-7-ones under Solvent-Free Conditions - Adib, Mehdi; Soheilizad, Mehdi; Zhu, Long-Guan; Wu, Jing (Synlett, 2015)
A one-pot, three-component synthesis of 3-(1H-pyrazol-1-yl)-4H,7H-[1,2,4,5]tetraazino[6,1-b][1,3]benzoxazin-7-ones is described which involves heating a mixture of 1,2-dihydro-3,6-bis(3,5-dimethyl-1H-pyrazol-1-yl)-1,2,4,5-tetrazine, aldehydes, and dimedone in the presence of a catalytic amount of p-toluenesulfonic acid under solvent-free conditions. The bridgehead-fused 6:6:6 systems with one ring-junction nitrogen atom were obtained in excellent yields.
Keywords: [1,2,4,5]tetraazino[6,1-b][1,3]benzoxazin-7-ones; 1,2-dihydro-3,6-bis(1H-pyrazol-1-yl)-1,2,4,5-tetrazine; solvent-free reaction; multicomponent reactions; cyclizations; heterocycles